The Productive Longevity Of Perennial Grasses Swards Depending On The Npk Fertilizer Rates (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The longevity and producing capacity of perennial grasses swards was studied on mineral soils at the LUA Research Institute of Agriculture in long-term experiment during 1974-2010. There were applied lime and mineral fertilizers with different NPK doses (0-400 kg ha-1) protractedly many years. In such way there formed soils with various content of P, K, organic matter content and pHKCl level as well. Research results showed that liming of soils and using of mineral fertilizer changed not only productivity of grass mixtures but also botanical composition. Mineral fertilizer N200P100K300 provided the highest yield of dry matter – 7.32 - 12.0 t ha-1 and optimal botanical composition of a sward during many years. On unlimed soils (pHKCL less then 4.0 in 1997) dry matter yields of grass sward was substantially lower and there was observed disappearance of seeded valuable grasses out of the sward and increase of herbs and non-seeded grasses –Festuca rubra L., Agrostis tenuis Sibth., Taraxacum officinale Wigg. and others. Liming of soils increased dry matter yield in treatments with high doses of N (300-400) fertilizer.